Running money : professional portfolio management - Stewart, Scott D. , 1958-; Heisler, Jeffrey C. , 1959-; Piros, Christopher D. (The McGraw-Hill/Irwin series in finance, insurance and real estate, 2011)
Focuses on the business investment decision-making from the perspective of the portfolio manager. This title intends to expose students to what it is really like to 'run money' professionally by providing the necessary tools